“ITULAH IBUMU” PENETAPAN KONSTITUTIF MARIA SEBAGAI BUNDA GEREJA: TELAAH BIBLIKAL ATAS TEKS YOH.19:25-27 - Dismas Turibius Neno; Siprianus Soleman Senda; Mikhael Valens Boy (Bahasa Indonesia, 2026)
One of the figures in the Bible who has an important role in the history of salvation is Mary. Mary's role began when she was called and chosen by God to conceive and give birth to the Word of God in the mystery of the Incarnation and her totality in accompanying Jesus in the work of His life until the fullness of Jesus' "moment" namely redemption on the cross. Mary's role is specifically contained in the four Gospels. Many studies have examined Mary's role from the perspective of the synoptic Gospels and the Gospel of John specifically in the aspects of holiness, discipleship and obedience. This research examines aspects of Mary's constitutive appointment as mother of the Church in the Gospel of John 19:25-27. The method used in this research is a literature study with a descriptive analysis approach to the text of John 19:25-27. Through this research, it was found that the text of John 19:25-27 can be interpreted as a theological basis that supports the appointment of Mary as Mother of the Church. The theological significance of the relationship between Mary, Jesus, and John on the cross brings a deeper understanding of Mary's role in the Church.